Income Analysis of Switching Paddy Farming to Maize in Wakadia Village, Watopute District, Muna Regency - Muhammad Ikbar; Azhar Bafadal; La Ode Kasno Arif (International Journal of Technology and Education Research, 2024)
This study aims to determine how the income of farming switch from field rice to hybrid corn. This research was conducted from December 2023 to July 2024 in Wakadia Village, Watopute Sub-district, Muna Regency The population in the study were all farmers who switched their farms from field rice to hybrid corn in Wakadia Village, totaling 165 people. Determination of the sample was determined by simple random sampling technique using the slovin formula, the sample in this study amounted to 60 respondents. The research used t test analysis tool. The results showed that hybrid corn farming income was greater than farming income from paddy fields, there was a significant difference in farmers' income before and after switching from paddy fields to hybrid corn